Pandangan Hakim PA Dan Ulama MUI Tentang Wasiat Wajibah Dalam Pewarisan Beda Agama - Margolang, Alifiah; Nasution, Muhammad Syukri Albani; Syam, Syafruddin (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
This study aims to determine the chronology of the contents of Jurisprudence Number 1/Yur/Ag/2018 which allows non-Muslim heirs to inherit by means of a mandatory will and the views of the judges of the Kisaran Religious Court and the Management of the Indonesian Ulema Council (MUI) of Asahan Regency. besides that, to describe it in the theory of Maqashid Asy-Syari'ah. This type of research is doctrinal research or juridical-normative research, using a case approach and a statute approach. The granting of obligatory wills to non-adopted children and adoptive parents has been consistently applied by the Supreme Court from 1998 to at least 2016. The views of the Religious Court judges and the Indonesian Ulema Council regarding non-Muslim heirs obtaining inheritance through the obligatory will are contradictory or mutually contradictory. each other. However, jurisprudence Number 1/Yur/Ag/2018 is a legal product that is decided for the benefit of humanity with legal justice.